1978
DOI: 10.1203/00006450-197810000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-Hydroxy-vitamin D in Familial Hypercholesterolemic Children Receiving Colestipol Resin

Abstract: Pediat. Res. 12: 980-982 (1978) Bile acid sequestrant resins (colestipol) 25-hydroxy-vitamin D SummaryIn this study we have assessed effects of Colestipol, a synthetic organic bile sequestrant polymer, on vitamin D metabolism over a 2-year period in children with familial hypercholesterolemia. In the 15 children, mean (+SE) low density lipoprotein (LDL) cholesterol decreased from 221 + 9 mg/dl (baseline), to 181 +-7 after 12-14 months of Colestipol resin, P < 0.01. Thereafter, LDL cholesterol remained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…One of the RCTs reported a statistically significant decrease in serum 25(OH)D concentrations among children with familial hypercholesterolemia taking 8 g cholestyramine/day for one year compared to controls 30 . In contrast, the time series and before-and-after studies reported no significant change from baseline circulating 25(OH)D levels among children taking colestipol for 2–24 months 32, 33 . Similarly, two of the RCTs both reported no significant differences in circulating 25(OH)D concentrations between adults taking 24 g cholestyramine/day and a control group after 24 weeks 31 or 7–10 years 29 .…”
Section: Drugs That Interfere With Vitamin D Absorptionmentioning
confidence: 80%
See 1 more Smart Citation
“…One of the RCTs reported a statistically significant decrease in serum 25(OH)D concentrations among children with familial hypercholesterolemia taking 8 g cholestyramine/day for one year compared to controls 30 . In contrast, the time series and before-and-after studies reported no significant change from baseline circulating 25(OH)D levels among children taking colestipol for 2–24 months 32, 33 . Similarly, two of the RCTs both reported no significant differences in circulating 25(OH)D concentrations between adults taking 24 g cholestyramine/day and a control group after 24 weeks 31 or 7–10 years 29 .…”
Section: Drugs That Interfere With Vitamin D Absorptionmentioning
confidence: 80%
“…Three RCTs (Class A; two neutral quality 29, 30 , one negative quality 31 ), one time series (Class C, negative quality 32 ), and one before-and-after study (Class D, negative quality 33 ) evaluated the effect of bile acid sequestrants on vitamin D status. One of the RCTs reported a statistically significant decrease in serum 25(OH)D concentrations among children with familial hypercholesterolemia taking 8 g cholestyramine/day for one year compared to controls 30 .…”
Section: Drugs That Interfere With Vitamin D Absorptionmentioning
confidence: 99%
“…28 A previous small study of colestipol in hypercholesterolaemic children with normal renal function did not demonstrate changes in phosphate, though the dif-ferences in patient population perhaps limit applicability to dialysis patients. 28 The treatment period was short, and the sample size was also limited. Overall, however, our results suggest that a larger and longer trial of colestipol as a phosphate-binding medication is feasible.…”
Section: Discussionmentioning
confidence: 93%
“…Further physiological studies measuring gut and/or urinary phosphate excretion as well as vitamin D status with colestipol treatment may be useful to clarify the effects of this drug on phosphate and also the mechanisms of action . A previous small study of colestipol in hypercholesterolaemic children with normal renal function did not demonstrate changes in phosphate, though the differences in patient population perhaps limit applicability to dialysis patients . The treatment period was short, and the sample size was also limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large double-blind randomized trial of patients treated with cholestyramine (24 g/day) for 4 months showed similar levels of vitamin D metabolites, PTH, and serum calcium and phosphate compared with placebo-treated patients [486]. Ismail et al showed equivalent findings after 6 months of therapy [464], as did long-term studies using another bile acid sequestrant, colestipol, for the treatment of children with familial hypercholesterolemia [487,488].…”
Section: Hypolipidemicsmentioning
confidence: 96%